2020
DOI: 10.3390/ani10091508
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Different Levels of Curcumin and Its Nanoparticles to Extender on Post-Thaw Quality of Cryopreserved Rabbit Sperm

Abstract: The cryopreservation process adversely affects sperm function and quality traits, causing some changes at biochemical and structural levels, due to mechanical, thermal, osmotic, and oxidative damage. Supplementation with curcumin nanoparticles could prevent and even revert this effect and could enhance the post/thawed sperm quality in the rabbit. The study amid to explore the effect of curcumin (CU) and curcumin nanoparticles (CUNPs) supplementation in semen extender on post/thawed rabbit sperm quality. Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 37 publications
6
57
0
1
Order By: Relevance
“…Zhu and colleague investigated the effects of supplementation of amin E analogue [ 64 ], cysteine [ 65 ], glutamine [ 66 ], trehalose [ 67 ] and melatonin [ 68 ], and revealed that supplementation of these antioxidative agents in Tris-citrate-glucose extender decreased ROS levels and improved the quality of frozen–thawed rabbit sperms. Fadl et al confirmed 1.0 mM melatonin improved the motility, viability, membrane and acrosome integrities, and DNA integrity of frozen–thawed rabbit sperms in different extender (INRA-82) [ 69 ] Additionally, curcumin and curcumin nanoparticles were confirmed to improve the post-thawed quality of rabbit sperms via redox signaling and reduce the apoptosis process [ 70 ]. On the other hand, Maya-Soriano et al reported that supplementation of bovine serum albumin, retinol and retinyl in the sperm freezing extender has no beneficial effect on the viability, mortality, progressivity, and acrosome and morphological integrity of frozen–thawed rabbit sperms at the concentrations they tested [ 71 ].…”
Section: Effects Of Supplementsmentioning
confidence: 99%
“…Zhu and colleague investigated the effects of supplementation of amin E analogue [ 64 ], cysteine [ 65 ], glutamine [ 66 ], trehalose [ 67 ] and melatonin [ 68 ], and revealed that supplementation of these antioxidative agents in Tris-citrate-glucose extender decreased ROS levels and improved the quality of frozen–thawed rabbit sperms. Fadl et al confirmed 1.0 mM melatonin improved the motility, viability, membrane and acrosome integrities, and DNA integrity of frozen–thawed rabbit sperms in different extender (INRA-82) [ 69 ] Additionally, curcumin and curcumin nanoparticles were confirmed to improve the post-thawed quality of rabbit sperms via redox signaling and reduce the apoptosis process [ 70 ]. On the other hand, Maya-Soriano et al reported that supplementation of bovine serum albumin, retinol and retinyl in the sperm freezing extender has no beneficial effect on the viability, mortality, progressivity, and acrosome and morphological integrity of frozen–thawed rabbit sperms at the concentrations they tested [ 71 ].…”
Section: Effects Of Supplementsmentioning
confidence: 99%
“…This emphasizes the importance of supplementing the freezing media with added antioxidants that would minimize the negative effect of ROS and maintain the quality of postthawed sperm (13). In this regard, different types of supplements are added to the freezing media as protective agents; however, antioxidants of natural origin are of special interest in this concern (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro processing and storage of semen leads to additional mechanical, thermal, osmotic, and oxidative stress inflicted on male gametes, which builds up a foundation for studies investigating the potential of CUR as an alternative supplement to semen extenders and cryopreservation media. According to an array on studies, CUR acted as an effective promoter of sperm motility in extended or cryopreserved rat [187], boar [188], bull [189], ram [190], rabbit [191], and human semen [192]. Furthermore, it was observed that CUR supplementation to semen extenders may lead to a lower percentage of alterations to the membrane integrity and acrosome stability [189,190,193,194] while the molecule exhibits a significant protection to the sperm mitochondrial activity, and thus enables a prolongation of the sperm vitality during liquid storage or cryopreservation [187,189,190].…”
Section: Curcuminmentioning
confidence: 99%